An Analysis of Actors in the Implementation of Public Policy on Accessibility of Persons with Disabilities for Work in Indonesia’s Special Region Yogyakarta - Muhammad Akbar Maulana; Dian Eka Rahmawati; Achmad Nurmandi (Universitas Medan Area, 2020)
This study aims to analyze the implementation of public policy on the accessibility of persons with disabilities to get a job in Yogyakarta. It focuses on the actors implementing the policy in the Indonesian region, namely the provincial government of Yogyakarta as the implementer and policymaker, private companies, and Non-Government Organization (NGOs), which should be the stakeholders of the policy, program, and activities in distributing labors with disabilities. To approach this problem, the researchers use the theory of Van Meter and Horn as a reference. Data have been collected through interviews and documentation that later on analyzed qualitatively with the software of NVivo 12 plus. This study concludes that providing employment opportunities for persons with disabilities has not been implemented optimally. First, it is due to the absence of aftercare services, namely follow-up assistance for persons with disabilities after participating in training and rehabilitation programs held by the Regional Government. Secondly, law enforcement in the policy implementation that is pro disabilities (inclusion) to private companies is not optimal. Third, the lack of coordination among the actors in the efforts of empowering persons with disabilities.